Diversification of behavior and postsynaptic properties by netrin-G presynaptic adhesion family proteins. Issue 1 (December 2016) - Zhang, Qi; Goto, Hiromichi; Akiyoshi-Nishimura, Sachiko; Prosselkov, Pavel; Sano, Chie; Matsukawa, Hiroshi; Yaguchi, Kunio; Nakashiba, Toshiaki; Itohara, Shigeyoshi
Abstract Background Vertebrate-specific neuronal genes are expected to play a critical role in the diversification and evolution of higher brain functions. Among them, the glycosylphosphatidylinositol (GPI)-anchored netrin-G subfamily members in the UNC6/netrin family are unique in their differential expression patterns in many neuronal circuits, and differential binding ability to their cognate homologous post-synaptic receptors. Results To gain insight into the roles of these genes in higher brain functions, we performed comprehensive behavioral batteries using netrin-G knockout mice. We found that two netrin-G paralogs that recently diverged in evolution, netrin-G1 and netrin-G2 (gene symbols:Ntng1 andNtng2, respectively), were responsible for complementary behavioral functions. Netrin-G2, but not netrin-G1, encoded demanding sensorimotor functions. Both paralogs were responsible for complex vertebrate-specific cognitive functions and fine-scale regulation of basic adaptive behaviors conserved between invertebrates and vertebrates, such as spatial reference and working memory, attention, impulsivity and anxiety etc. Remarkably, netrin-G1 and netrin-G2 encoded a genetic "division of labor" in behavioral regulation, selectively mediating different tasks or even different details of the same task. At the cellular level, netrin-G1 and netrin-G2 differentially regulated the sub-synaptic localization of their cognate receptors and differentiated the properties of postsynaptic scaffold proteins in complementary neural pathways. Conclusions Pre-synaptic netrin-G1 and netrin-G2 diversify the complexity of vertebrate behaviors and differentially regulate post-synaptic properties. Our findings constitute the first genetic analysis of the behavioral and synaptic diversification roles of a vertebrate GPI protein and presynaptic adhesion molecule family.